Rancang Bangun Pengatur Cermin Sebagai Komponen Gerak Interferometer Pada Spektroskopi FTIR - Adi Wibowo, Wahyu; Edi Widodo, Catur; Azam, M.; Firdausi, K. Sofjan (BERKALA FISIKA, 2008)
Michelson's interferometer and mirror regulator system as components of its power have been designed. Interferometers stirred component is one of monotonic mirror on optic system. Interferometer is made accords Michelson's Interferometer attempt. Mirror M1 and mirror M2 is assembled mutually upright then one beam splitter placed before both of mirror. One laser light source is given before mirror M1 crosses beam splitter. There is a detector before mirror M2 crosses beam   splitter upright with laser light source. Mirror M1 is made flexible by assembled gear and stepper's motor to be able forward or backward motion then so called moveable mirror.  Stepper's motor is turned around by computer via parallel port. From interferometer engineering and mirror regulator system already been made, gotten interference pattern with ring amount that the less each mirror gets forward motion and ring amount that more and more each mirror moves to backward. Shift moveable mirror every step for forward or backward is 1,5 µm with distance sails through maximal be 6,0 mm. The in common result point out that interferometer and regulator system of moveable mirror show feature changed interference pattern along with mirror move. Key word: interferometer, moveable mirror, motor stepper, parallel port.